Local Determinants of Population Ageing in Poland - Kula, Grzegorz; Wójcik, Piotr Tadeusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Polish population is getting older and the consequences of this process are already affecting our everyday life. The purpose of this work is to identify factors (and direction of their influence) which will help to explain why some counties are ageing faster than others. Using a measure of spatial autocorrelation (Moran’s I) and spatial autoregressive model on panel data we analyze characteristics of Polish counties in the period 2003–2013. The dependent variable is the share of old people in the population of municipality (in the age of 70 and older). Results indicate strong spatial autocorrelation, which means that population ageing in particular county is strongly related to the speed of ageing in the neighboring counties. Many additional socio‑demographic characteristics of municipalities appear to be important in explaining the analyzed phenomenon, including transportation network (motorways and express ways) that link a particular county with other regions.